Optimizing influenza prevention: a systematic review of the cost-effectiveness of pediatric vaccination programs and vaccine types - Aksoy, Nilay; Ozturk, Nur; Agh, Tamas; Kardas, Przemyslaw; Şahin, Bayram (Frontiers in Public Health, 2025)
IntroductionSeasonal influenza is a major cause of illness and death worldwide. Vaccination remains the cornerstone of prevention, with options including trivalent inactivated (TIV), quadrivalent inactivated (QIV), and live-attenuated vaccines. This study aimed to provide a systematic overview of the cost-effectiveness of pediatric influenza vaccination programs, with a particular focus on comparing different vaccine types.MethodsA comprehensive literature search was conducted in PubMed, Web of Science, Scopus, and Cochrane databases for records published between 2013 and 2024. The target population included individuals younger than 18 years. The primary research question was: Which influenza vaccines, trivalent, quadrivalent, or live-attenuated, are more cost-effective, and how does introducing seasonal vaccination for children under 18 influence healthcare costs and health outcomes? Data extraction was performed using a structured Excel spreadsheet.ResultsThis review included 33 studies that met the inclusion and exclusion criteria. Most studies support the conclusion that vaccinating children is an effective and cost-effective strategy for reducing influenza transmission. Cost-effectiveness varied depending on epidemiological and demographic factors, the type of vaccine used, and age group differences, which were influenced by the analytical perspective and local health and economic conditions.ConclusionThis review confirms that pediatric influenza vaccination is a cost-effective intervention, particularly with quadrivalent vaccines. The optimal choice of vaccine and strategy should be tailored to local population needs and economic conditions to maximize public health benefits.